2020
DOI: 10.20944/preprints202001.0238.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Geochemical, Mineralogical and Morphological Characterisation of Road Dust and Associated Health Risks

Abstract: Road dust resuspension, especially the particulate matter fraction below 10 µm (PM10), is one of the main air quality management challenges in Europe. Road dust samples were collected from representative streets (suburban and urban) of the city of Viana do Castelo, Portugal. PM10 emission factors (mg veh-1 km-1) ranging from 49 (asphalt) to 330 (cobble stone) were estimated by means of the United Stated Environmental Protection Agency method. Two road dust fractions (< 0.074 mm and from 0.0074… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The relative OC levels of total PM mass were higher in the fine than coarse PM samples, constituting around 50–60% and 10–15% of the total mass of the respective size-fractions. This may reflect that coarse PM is usually dominated by road dust which consists primarily of mineral particles [ 51 , 52 ], while fine and ultrafine PM consist primarily of particles from combustion sources [ 26 ]. The OC content in the PM samples seemed to be relatively high in comparison to other studies reporting ratios of OC/PM in air from European cities for PM 2.5 and PM 10 [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relative OC levels of total PM mass were higher in the fine than coarse PM samples, constituting around 50–60% and 10–15% of the total mass of the respective size-fractions. This may reflect that coarse PM is usually dominated by road dust which consists primarily of mineral particles [ 51 , 52 ], while fine and ultrafine PM consist primarily of particles from combustion sources [ 26 ]. The OC content in the PM samples seemed to be relatively high in comparison to other studies reporting ratios of OC/PM in air from European cities for PM 2.5 and PM 10 [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mn in roadway dust links to traffic emissions (Straffelini et al, 2015), where Mn is employed in fuel additives, anticorrosion, and other automobile applications (inner panels, heater, and radiator tubes) (Candeias et al, 2020). Apeagyei et al (2011) found metal concentrations in brake pads in the following order: Mn>Zn>Pb>Cr>Cd.…”
Section: Metal Pollution Indicesmentioning
confidence: 99%
“…The UAE is one of the largest consumers of fertilizers, with a consumption rate of 643.4 kg/hectare of arable land in 2020 compared to the world average of 180.1 kg/hectare (Economy, 2020). Arsenic is associated with pesticide application, organic manure, and phosphatic fertilizers (Candeias et al, 2020) commonly used in these farms. In addition to agricultural sources of As in this area, As is originated from motor-related non-exhaust emissions as the elemental As is employed in manufacturing Pb alloys (in Pb-acid batteries) and Cu (Office of Air Quality Planning And Standard, 1998; Agency for Toxic Substances and Disease Registry ATSDR, 2007).…”
Section: Metal Pollution Indicesmentioning
confidence: 99%
“…This is especially problematic in Nordic countries due to the widespread use of studded tyres during winter, which increases road-surface abrasion [ 36 , 38 , 40 ]. While the mineralogy of road dust and ambient PM is not commonly assessed, some studies have reported the presence of several different types of minerals, including quartz, feldspars, mica and various clay minerals [ 41 43 ]. However, the contribution of the mineral fraction to PM-induced diseases is not fully known.…”
Section: Introductionmentioning
confidence: 99%